FAMILY EXPERIENCES IN TREATING CHILDREN WITH HIV/AIDS THROUGH ARV THERAPY IN JAYAPURA CITY - Suryati Romauli; Sri Wahyuni (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
Background: HIV / AIDS infected more than 90% of children in 2017, acquired from their mothers. In accordance, special protection from families is crucial. Antiretroviral is the best therapy in PLWHA children’s treatment, and family support is needed to succeed. Objective: To explore in detail family experiences in nurturing HIV / AIDS children with ARV therapy in Jayapura City. Methods: This research is qualitative research with a phenomenology approach. The selection of participants was obtained by purposive sampling, and 8 participants were selected to be interviewed using voice recorder and file notes. Data were analyzed using nine stages of Colaizzi. Results: There are five themes, namely: the initial obstacles faced by the family of ODHA children; Family efforts to care for children living with HIV / AIDS; Constraints in child care; Form of health care workers; Fulfilling physical, psychological, and laboratory needs. Conclusion: Participants lacking in knowledge regarding HIV / AIDS. Consequently, it became the major obstacle faced by families of ODHA children, this affecting delayed child's HIV status, but in terms of child care, there is a lot of support for children